Two new Larainae species from Guayana region, Venezuela (Coleoptera: Elmidae) - Laššová, Kristína; Čiampor, Fedor Jr; Čiamporová-Zaťovičová, Zuzana (Zootaxa, 2013)
Two new species of the subfamily Larainae (Insecta: Coleoptera: Elmidae), Hexanchorus angeli n. sp. and Hypsilara autanai n. sp., are described from Guyana region in Venezuela. We provide habitus photographs, detail drawings of both male and female genitalia, and description of morphological features important for discrimination of the new species. Molecular differences within genera were measured using 816bp fragment of mtDNA gene for cytochrome oxidase c subunit I. Sequence divergences among species are discussed.